Gambaran Penyesuaian Diri Narapidana Pria Di Lembaga Pemasyarakatan Cipinang - Egabetha Amirah Yudhaputri; Venie Viktoria Rondang Maulina (Fakultas Psikologi Universitas Pancasila, 2012)
Adjustment is the process of habituation to the changes experienced by everyone. For inmates, adjustment process is a period when entry and detention in prison. Inmates lose freedom as a human being, which will live in prison and environmental regulations that are different from the life that used to be felt outside the prison. In addition, inmates will experience a variety of problems associated with the physical environment and the social environment in prisons. This study is a qualitative research. Subjects used in this study were male inmates in Lapas Cipinang. Number of subjects in this study were four people. Characteristics of the subjects are based on the length of detention and prisoners who first entered prison. Data collection was done by interviews. This study concluded that the four subjects had a different adjustment experienced. In addition, four subjects facing different problems in prison. Some subjects can solve problems and adapt, but the others also have a conflict during the process of adjustment.